THE EFFECT OF USING CALCIUM SOAP IN THE RATION ON THE BLOOD LIPID PROFILE OF MALE BALI DUCKS - N.P., Aryanti; Puspani, E.; Candrawati, D.P.M.A. (Jurnal Peternakan Tropika, 2022)
This study aimed to determine the effect of calcium soap supplementation in the diet on the blood lipid profile of 8 weeks old male bali ducks.  This research took place for 6 weeks in a duck cage owned by a breeder located on Jl. Tegal Wangi 2, Gang Plot No. 9, Sesetan Village, Denpasar City, Bali. The design used was a completely randomized design (CRD) with 4 treatments and 6 replications, so there were 24 experimental units.  Each experimental unit used 4 ducks aged 2 weeks with homogeneous body weight. The four treatments were male bali ducks fed a control ration without calcium soap (A), male bali ducks given 1% calcium soap (B), male bali ducks fed 2% calcium soap (C), and male bali ducks.  Who were given a ration of 3% calcium soap (D).  The variables observed were high density lipoprotein (HDL), low density lipoprotein (LDL), triglycerides, and total cholesterol.  Total cholesterol levels of male bali ducks in treatment B, C and D were significantly lower (P<0.05) than treatment A.  Triglyceride levels that received treatment B and C were not significantly different (P>0.05) lower than treatment A, while treatment D was significantly different (P<0.05) lower than treatment A.  The results of HDL and LDL levels were not significantly different (P>0.05).  The results of this study can be concluded that calcium soap supplementation in the ration can reduce total cholesterol and triglyceride levels, and has no effect on HDL and LDL levels in male bali ducks.   Keywords: male bali duck , blood lipid profile, calcium soap